Design and Development of Docetaxel Solid Self-Microemulsifying Drug Delivery System Using Principal Component Analysis and D-Optimal Design (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this research was to develop a solid self-emulsifying drug delivery system for BCS Class IV drug (Docetaxel) using Principal component analysis (PCA) and D-Optimal Design (cubic model). To convert liquid self-emulsifying drug delivery system in solid dosage form, the liquid-solid compact (LSC) technique was used and in vitro dissolution rate was increased up to 60 min. Materials and Methods: The Docetaxel liquid self-emulsifying drug delivery system was prepared by considering oleic acid as oil phase (42.37%), Tween-80 (43.39%) as a surfactant, and PEG-400 (14.21%) as cosurfactant. The pseudoternary phase diagram was plotted using Chemix School 7.0 software, and microemulsion region was spotted. Now, using PCA (Using The Unscrambler®X software) emulsification time and % cumulative drug release at 30 min were selected as two most important variables which were considered for preparing self-microemulsifying drug delivery system (SMEDDS) using D-Optimal Design (Design-Expert® V10). From the design output and desirability function, it was identified that among 16 batches DOXP-13 was coming out as a best-optimized batch. The optimized batch was further characterized by high-performance liquid chromatography (HPLC) method and its polydispersity index (PDI), zeta potential, and droplet size were determined. The optimized microemulsion was further converted into a 250 mg solid tablet using the LSC technique by considering HPMC K100LV (Methocel) as carrier and magnesium trisilicate as a coating agent. From differential scanning calorimetry and infrared studies, it was confirmed that no possible interaction was observed between liquid SMEDDS and carrier and coating materials of the LSC. The 250 mg final tablet (LSC-Tab) was kept for 1-month stability studies. Results and Discussion: From the solubility studies, it was confirmed that oleic acid with 413.66 mg/g has a higher Docetaxel solubility among all the oils. Same way, tween-80 (299.61 mg/g), PEG 400 (462.86 mg/g) has a maximum solubility with Docetaxel. The optimized DOXP-13 batch has shown 19.71 ± 0.08 seconds emulsification time and 95.21 ± 0.01% cumulative drug release at 30 min. From the HPLC studies, it was observed that Docetaxel SMEDDS has 103.23% w/v recovery and 9.180 min as retention time. The zeta potential of the DOXP-13 optimized batch was found to be 0.034mv with 0.218 PDI and 100.8nm zeta diameter. The mean droplet size of the SMEDDS was found to be 2.346μm. During conversion of liquid SMEDDS into solid, the optimum flowable liquid retention potential (Ø) at a 33° angle was found to be 0.80. The final 250 mg tablet (LSC-Tab) disintegration time was found to be 42 ± 0.20 min. LSC-Tab shows 100.39 ± 0.39% cumulative drug releases at 60 min. From the 1-month stability studies, it was confirmed that LSC-Tab has good stability with good dissolution profile. Conclusion: It can be concluded that Docetaxel loaded solid self-microemulsifying drug delivery system was successfully prepared, and solubility and dissolution of Docetaxel were improved.